Inflammatory Determinants of Pregravid Obesity in Placenta and Peripheral Blood - Sureshchandra, Suhas; Marshall, Nicole E.; Wilson, Randall M.; Barr, Tasha; Rais, Maham; Purnell, Jonathan Q.; Thornburg, Kent L.; Messaoudi, Ilhem (Frontiers in Physiology, 2018)
Pre-pregnancy (pregravid) obesity has been linked to several adverse health outcomes for both mother and offspring. Complications during pregnancy include increased risk for gestational diabetes, hypertension, preeclampsia, placental abruption, and difficulties during delivery. Several studies suggest that these negative outcomes are mediated by heightened systemic inflammation as well as changes in placental development and function. However, the molecular mechanisms by which pregravid obesity affects these processes are poorly understood. In this study, we aimed to address this question by carrying out a comprehensive analysis of the systemic maternal immune system coupled with placental gene expression and microbial profiling at term delivery (11 lean and 14 obese). Specifically, we examined the impact of pregravid obesity on circulating cytokines, chemokine, adipokines, and growth factors using multiplex Luminex assay. Innate and adaptive immune cell frequencies and their cytokine production in response to stimulus were measured using flow cytometry. Finally, changes in placental transcriptome and microbiome were profiled using RNA- and 16S-sequencing respectively. Pregravid obesity is characterized by insulin and leptin resistance, high levels of circulating inflammatory markers IL-6 and CRP, in addition to chemokine IL-8 (p <0.01). Moreover, pregravid obesity was associated with lower frequency of naïve CD4+ T-cells (p <0.05), increased frequency of memory CD4+ T-cells (p < 0.01), and a shift towards Th2 cytokine production (p=0.05). Myeloid cells from the obese cohort produced higher levels of pro-inflammatory cytokines but lower levels of chemokines following TLR stimulation (p <0.05). Lastly, pregravid obesity results in with increased abundance of Bacteroides and changes in the expression of genes important for nutrient transport and immunity (FDR <0.05). Collectively, these data indicate that pregravid obesity is associated with heightened systemic inflammation and of dysregulated nutrient transport in the placenta and provide insight into the basis of fetal reprogramming.